2024
DOI: 10.26599/fshw.2022.9250051
|View full text |Cite
|
Sign up to set email alerts
|

Ganoderma lucidum: a comprehensive review of phytochemistry, efficacy, safety and clinical study

Abstract: Ganoderma lucidum (G. lucidum), one of the most well-known edible fungi, is believed to be very beneficial for longevity and vitality. A long usage history suggests that G. lucidum has various clinical therapeutic effects. And experimental studies have confirmed that G. lucidum has multiple pharmacological effects, including antitumor, anti-microbial, anti-HIV protease, and antidiabetic activity and so on. With the deepening of research, more than 300 compounds have been isolated from G. lucidum. There is an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 359 publications
0
18
0
Order By: Relevance
“…Several research works have reported different secondary metabolites from the Ganoderma genus, particularly from the G. lucidum species ( Zhou et al, 2012 ; Sharma et al, 2019 ; Lu Y. et al, 2020 ; Wu et al, 2024 ), with interesting bioactivities. In this context, Baby et al (2015) reviewed the biologically active secondary metabolites produced by different species belonging to the Ganoderma genus.…”
Section: Biologically Active Secondary Metabolites Produced By White-...mentioning
confidence: 99%
“…Several research works have reported different secondary metabolites from the Ganoderma genus, particularly from the G. lucidum species ( Zhou et al, 2012 ; Sharma et al, 2019 ; Lu Y. et al, 2020 ; Wu et al, 2024 ), with interesting bioactivities. In this context, Baby et al (2015) reviewed the biologically active secondary metabolites produced by different species belonging to the Ganoderma genus.…”
Section: Biologically Active Secondary Metabolites Produced By White-...mentioning
confidence: 99%
“…Ganoderma lucidum , also known as Lingzhi or Reishi, is a fungal species belongs to the Ganodermataceae family ( 1 ). This fungus is a well-recognized medicinal mushroom, and holds a prominent position in traditional Chinese medicine for centuries due to its health benefits ( 2 ). The medicinal properties of G. lucidum has been extensively studied and documented in numerous literatures.…”
Section: Introductionmentioning
confidence: 99%
“…G. lucidum possesses a diverse array of bioactive constituents that contribute to its therapeutic effects. This fungus is a rich source of triterpenes, polysaccharides, steroids, nucleotides, fatty acids, and other active secondary metabolites ( 2 , 9 , 10 ). Among these phytochemicals, the triterpenes, particularly the ganoderic acids and lucidenic acids, have been extensively studied and recognized for their pharmacological significance ( 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…This fungus has long been utilized as a medicinal and edible fungus due to its various bioactive components [ 56 , 57 ]. Its chemical composition includes polysaccharides, triterpenes, nucleosides and other active substances [ 58 , 59 ], granting it sedative, hypnotic, anti-inflammatory and anti-diabetes properties [ 60 , 61 ]. It has traditionally been employed in the treatment of restlessness, insomnia and other health issues [ 62 ].…”
Section: Introductionmentioning
confidence: 99%